Calendar effect in Malaysia stock market / Amelia Zasha Arman Shah - Arman Shah, Amelia Zasha (2017)
This paper investigates the existence of the monthly effect in the Malaysia stock market between January 2004 and December 2015. The sample size is 144 and the data was obtained monthly. The data was partitioned into two-time frame which is sub-period basis and full period basis. For sub-period basis, it was partitioned into three sub-periods which is pre-crisis period, crisis period and post-crisis period during the Global Financial Crisis while for full period basis it is partitioned into eleven months which is from January until November and used December as its benchmark. This research has failed to provide the existence of monthly effect in Kuala Lumpur Composite Index for the three sub-periods. However, when the full period was examined, the regression results found that the returns are negative and significant for August during the full period.